Slang Analysis in Film "Fury" - Iswan Aramiko; Usman Kasim; Zulfadli A. Aziz (English Education Journal, 2019)
The aims of this research are to identify the functions, types and the formation of slang words/phrases in the film “Fury”. This research is qualitative research with content analysis design. The data are slang words/phrases from the conversations of the film. The data were collected through observation with observation guide as the instrument. The result of the research shows that the functions of using slang in the film were to show emotion, rebellion, humor, toughness, creative, vibrant, informality, stylization, conciseness, and forcefulness. The types of slang used in the film were hip-hop slang, slang in University of Leicester, inner city slang of New York, general slang, and specific slang. The slang words/phrases in the film were formed by suffixation, final combining, reversed form, compounding, clipping, and word manufacture.